Effect of laser rescanning on Ti6Al4V microstructure during selective laser melting. (April 2021) - Duan, Weipeng; Wu, Meiping; Han, Jitai
TC4, which is one of the most widely used titanium alloy, is frequently used in biomedical field due to its biocompatible. In this work, selective laser melting (SLM) was used to manufacture TC4 parts and the printed parts were heat-treated using laser rescanning technology. The experimental results showed that laser rescanning had a high impact on the quality of SLMed part, and a different performance on wear resistance can be found on the basis. It can be seen that the volume porosity of the sample was 7.6 ± 0.5% without using any further processing technology. The volume porosity of the sample processed using laser rescanning strategy was decreased and the square-framed rescanning strategy had a relative optimal volume porosity (1.5 ± 0.3%) in all these five samples. With the further decreasing of volume porosity, the wear resistance decreased at the same time. As its excellent bio-tribological properties, the square-framed rescanning may be a potential suitable strategy to forming TC4 which used in human body.